2011
DOI: 10.4041/kjod.2011.41.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tumor necrosis factor-α levels around miniscrews during canine distalization

Abstract: Objective: The aim of this study was to measure tumor necrosis factor-α (TNF-α) levels around miniscrews used for anchorage during a 3-month period of canine distalization. Methods: Sixteen patients (8 boys, 8 girls; mean age, 16.6 ± 2.4 years) whose upper first premolars were extracted for orthodontic treatment were included in this study. Miniscrews were used as an anchorage unit in canine distalization. Thirty-two (32) miniscrew implants were placed bilaterally in the alveolar bone between the maxillary sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Thirty-nine shortlisted studies [ 19 , 22 - 59 ] were scrutinized for inclusion and exclusion criteria. Two studies that evaluated mediators both in peri-implant crevicular fluid (PMICF) as well as GCF were included [ 51 , 54 ] but one study that evaluated the levels of mediators directly in sulcus and not GCF was excluded [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty-nine shortlisted studies [ 19 , 22 - 59 ] were scrutinized for inclusion and exclusion criteria. Two studies that evaluated mediators both in peri-implant crevicular fluid (PMICF) as well as GCF were included [ 51 , 54 ] but one study that evaluated the levels of mediators directly in sulcus and not GCF was excluded [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies on IL-1β were evaluated. Of these, ten studies (N = 10) reported that the peak levels of IL-1β were attained at 24 h [ 19 , 22 , 27 , 33 , 37 , 42 , 50 , 51 , 53 , 54 ]. The peak levels in other studies have also been reported at 4 h [ 47 ], 3 days [ 35 , 40 ], 7 days, 21 days [ 29 ], 2 months [ 22 ], around 3 months [ 39 , 46 ], and 6 months [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations